Incidence and Predictors of Pulmonary Tuberculosis among Children Who Received Antiretroviral Therapy (ART), Northwest Ethiopia: A Multicenter Historical Cohorts Study 2009–2019. (29th January 2022) - Kebede, Fassikaw; Tarekegn, Habtamu; Molla, Mulugeta; Jara, Dube; Abate, Abebe
Abstract : The human immune deficiency virus (HIV) is the strongest risk factor for endogenous reactivation of pulmonary tuberculosis (PTB) through target reduction of CD4, T-lymphocytes, and cellular immune function. Almost one-third of deaths among people living with HIV are attributed to tuberculosis. Despite this evidence, in Ethiopia, information is scarce and meager regarding PTB incidence after ART initiated for seropositive children. Methods . Facility-based multicenter historical cohort was conducted among 721 seropositive children after initiating ART from January 1, 2009, to December 31, 2019. Data from the records of children were extracted using a standardized checklist. The collected data were entered using Epi-Data version 4.2 and exported to STATA (SE) R-14 version statistical soft wares for further analysis. Bivariable and multivariable Cox regression analyses were conducted to identify predictors of PTB incidence. Results . Seven hundred twenty-one ( N  = 721) seropositive children were included with a mean (±SD) age of 118.4 ± 38.24 months. During the follow-up periods, 63 (15.2%) participants developed new cases of TB; majority (61/63, 96.8%) of them were PTB. The overall incidence rate and the median (±IQR) time of PTB reported were determined as 5.86 per 100 child years (95% CI: 4.58, 7.5) and 17.8 (±11) months, respectively. At baseline, children being severely stunted (AHR = 2.9 : 95% CI, 1.2–7.8, P = 0.03 ), with Hgb ≤10 mg/dl (AHR = 4.0; 95% CI, 2.1–8.1, P = 0.001 ), and not given isoniazid and cotrimoxazole preventive therapy (AHR = 2.4; 95% CI: 1.2; 5.1, P = 0.001 ) (AHR = 2.5; 95% CI, 1.4–4.7, P = 0.021 ) were significantly associated with PTB incidence. Conclusion . A high incidence rate of PTB was observed in our study as compared with the previous finding in Ethiopia. Cases at baseline not taking IPT and CPT, being severely stunted, and having low hemoglobin (≤10 mg/dl) levels were found to be at higher risk of developing PTB.